EFEKTIFITAS PELAYANAN PUBLIK PENERBITAN IZIN USAHA DI KOTA BAUBAU - Farid Yusuf Nur Achmad (Kybernan: Jurnal Studi Kepemerintahan, 2016)
This study aims to determine how the effectiveness of publishing services business license in Licensing Service Agency and Investment Baubau city as well as to determine the factors that hinder the effectiveness of publishing services business license in Licensing Service Agency and Investment Baubau City. Study is a qualitative descriptive study, the research done by examining primary and secondary data. The population in this research that all employees at the Agency for Investment and Licensing Services Baubau city as many as 33 people. The sampling technique using total sampling. Data collection techniques are: observation, interviews, literature study and documentation. Processing and presentation of data by using data reduction, data presentation and verification of data. Data sources are: Primary and Secondary, Technical Analysis used in this research is qualitative descriptive analysis. Results of the study are: publishing services business license in Licensing Service Agency and Investment Baubau city is said to be effective, the factors that hinder the effectiveness of publishing services business license Licensing Service Agency and Investment Kota Baubau namely: the factor of time, cost factor and requirements in the licensing service , In an effort to streamline the process of licensing services to the public the government is expected to further the transparency of financial reasons that one way to do expose the online and offline media. In the matter raising public awareness as users of government services shall direct socialization in employers-local businessmen in an effort to take advantage of local entrepreneurs. Penginkatan performance and resource officers, the government in this case the service provider must also accept criticism and suggestions from users are a good and wise.